Republic of Congo : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2014)
KEY ISSUES Economic context. Growth has been strong, inflation low, and fiscal buffers and international reserves adequate. However, poverty and unemployment remain high, despite large government spending financed from oil revenue. The business climate is among the most challenging and the private credit-to-GDP ratio among the lowest in sub-Saharan Africa (SSA). Outlook and Risks. The economy is projected to expand by about 6 percent per annum between 2014 and 2019, as new oil fields come on stream and an ambitious public investment program is implemented to diversify the economy and make growth more inclusive. Oil production is expected to peak in 2017. The medium-term outlook for non-oil growth and poverty reduction hinges on progress addressing deep-seated structural weaknesses and fiscal adjustment. Risks to the outlook relate to oil price volatility and political instability. Policies. Macroeconomic policies should focus on meeting the economy's social and development needs while mitigating risks to macroeconomic stability in the longer term. -- The growth of government spending should be arrested and the 2014 budget should not be exceeded. Amid spending pressures related to the 2015 Africa Games and the 2016 presidential elections, new fiscal developments should be reflected in a supplementary budget in 2014 to enhance transparency. -- In view of the limited remaining lifetime of oil reserves, a gradual fiscal consolidation should be targeted over the medium-term to safeguard fiscal and debt sustainability. Ongoing efforts to address implementation and absorptive capacity constraints need to be stepped up to maximize the benefits from public investments. -- Consideration should be given to adopt the non-oil primary balance as the fiscal anchor. -- The private sector's supply response to public infrastructure spending should be maximized through implementation of reforms to improve the business climate, support private investment, and develop the financial sector. -- The pilot project for cash transfers should be well-targeted and monitored to reduce poverty. -- Compliance with reserves pooling requirements would insure the continued smooth operation of the BEAC and the exchange rate peg, which both continue to serve the Republic of Congo well.